Strategic actions agenda for reducing congenital syphilis in Brazil: a multi-party, shared initiative - Benzaken, Adele Schwartz; Toledo, João Paulo; Cavalcanti, Adeilson Loureiro; Freitas, Francisca Lidiane Sampaio; Santos, Itana Miranda dos; Tresse, Alexsana Sposito; Gonçalves, Maria Vitória Ramos (Brazilian Journal of Sexually Transmitted Diseases, 2016)
Syphilis is a curable and systemic sexually transmitted infection (STI) caused by Treponema pallidum bacteria. When left untreated, it progresses into different clinical manifestations that may last many years. Early syphilis includes the primary, secondary, and latent stages, while late syphilis comprises the late-latent and tertiary stages. Transmission via sexual intercourse is more common in the early stages and gradually decreases over time. It remains, however, transmittable from mother to fetus, most often within the uterus, potentially leading to abortion, preterm delivery, congenital manifestations, or even newborn death(1). Having one STI increases the risk of acquiring HIV by two or three times.(2) [...]